Characteristics of Motorcyclists in Baghdad City - Mohamedmeki, Mohammed Zuhair; Al-Mumaiz, Maha (Journal of Engineering and Sustainable Development, 2026)
In recent years, Baghdad City has experienced a remarkable increase in the number of motorcyclists. Considerable numbers of motorcyclists are driving against the direction of traffic flow. This has had a negative impact on the safety of roads network. Based on that, studying the characteristics and performance of those users is essential. To collect the required data, a questionnaire was designed and distributed to motorcyclists. The results revealed that most of the motorcyclists in Baghdad are in the age group 20 to 30 years old; about 80% are not wearing helmets, 10% have no level of education, and most have had accidents of varying severity. Managing this safety problem required a collaboration of different authorities. A framework of requirements to improve motorcyclists’ safety in Baghdad city was proposed. In addition, a road network modification was presented by selecting suitable roads in Baghdad city to be used for creating an exclusive lane for the proposed motorcyclists’ network. Besides that, the geometric and marking enhancements of current intersections.